L’APPARENZA DEL SOGNO E DELL’AMORE NELLA MORSA DELLA REALTÀ: LA CONDIZIONE DELLA DONNA E DELL’UMANITÀ NELL’OPERA DI LUIGI PIRANDELLO E NELLE SUE RIVISITAZIONI - Varone, Giuseppe (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The essay highlights how Luigi Pirandello’s work, actualized in its various reinterpretations over the course of the 2000s, of which only a few are given as examples, is a reflection of the contradictions of the world and humanity, embodied mostly in the characters: unhappy individuals without ideals, placed in a precise era and social context, the petty and middle bourgeoisie of the early 20th century, though endowed with a universal character, capable of transcending time and historical fact. All of Pirandello’s dramatic art responds to the desire to bring to the page and the theatrical stage such an insight: the conception of existence as an enduring disagreement between face and mask, thus between reality and fiction. And the first of all feelings to fall into the grip of appearances is love, which, like the dream, in the mechanisms of bourgeois social life loses its naturalness and becomes illusion and condemnation. The appearance of love, therefore, provides the possibility of reading the world in the terms of a perennial conflict between ideal and real, and it is noted how the dreamlike universe concretely affects reality, with traumatic consequences that lack a rational explanation: not coincidentally, madness for Pirandello is a long dream and the real mystery of the world is the visible.